Overhauling America's healthcare machine : stop the bleeding and save trillions - Perednia, Douglas A. (FT Press, 2011)
Even after Obama, America's healthcare system is still broken, and it will soon bankrupt us all. The solution: radical simplification. Now, the author a healthcare expert and entrepreneur reveals the system's shocking, unnecessary inefficiencies, and outlines a simple, logical, complete solution that offers greater security, enhances competition, and will save trillions.